Formation of copper-based particles trapped in a silica xerogel matrix - G. Ortega Zarzosa (Superficies y vacío, 2000)
Using IR absorption and X-Ray diffraction we have analyzed the incorporation of Cu-based aggregates in a SiO2 matrixin samples prepared by the sol-gel method. We doped the silica xerogels samples using two different copper sources:Cu(NO3)2·2.5H2O and copper particles chemical synthesized. The samples were studied as a function of annealingtemperature. It is found that the by heat treatment and the appropriate copper precursor we can produce particles ofmetallic Cu, cuprous and cupric oxide. The obtained IR absorption results allow studying the interaction of the metalbasedspecies and the oxide support